Kratek priročnik znakovnega jezika: Breaking the Silence (University of Maribor Press, 2017)
A Brief Guide of Sign Language. We live in times where communication and its means almost seem to be limitless. Communication has become such an important and ever-present part of our everyday that it can sometimes be overwhelming. At the same time, we are, paradoxically, faced with progressively more difficult problems in terms of communication, due to many reasons, on an interpersonal as well as professional level. One of these reasons presents partial hearing loss and deafness. The project Breaking the silence (BTS), which represents one of the activities of the Slovenian medical student’s international committee Maribor, has therefore prepared this short handbook/guide on sign language. Our aim was to offer some help to medical practitioners in communicating with deaf patients, call attention to the need for education in terms of sign language in the medical field as well as stress the importance of good verbal and nonverbal communication in all aspects of our life.